Philosophy of technology, approaches, views and erroneous perceptions, an explanation of the philosophy of educational technology in the present era - H. Fardanesh; A. Jamshidi Tavana (Fanāvarī-i āmūzish, 2015)
Technology category contains different ideas and approaches. Despite different beliefs and approaches, some experts, restricted technology and philosophy of technology in two approaches "instrumentational" and "civilization". In addition, "advanced" or "lack of advanced" Suggest According time  priority and recency; So that approach for  time priority knows the truth and previous approach knows retrogressive. In this article, following the introduction of brief history of the evolution of this issue that can be expressed; then the views and categories of philosophy of technology are discussed. The result shows that there are several approaches and philosophy of technology, these approaches and beliefs are discussed at a level and surface, time cannot be based on the criteria for preferring one over the other.